VD_FINDINFO HC / 2012 / 180 vom 14. März 2012 - VD Tribunal cantonal (2012)
TRANSACTION JUDICIAIRE, DÉCISION SUR FRAIS, ASSISTANCE JUDICIAIRE | 165 al. 1 TFJC, 109 CPC (CH), 122 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH)